From J Thai Rehabil Med to ASEAN J Rehabil Med - โฆวินทะ อภิชนา (ASEAN Journal of Rehabilitation Medicine, 2019)
As a peer review medical journal, the J Thai Rehabil Med (ISSN: 2630-0184) has been accepted for its publication standards by the Thai citation index (TCI) and in 2016 it was accepted by the ASEAN (Association of Southeast Asian Nations) citation index (ACI). The latter made us consider changing the title of the Journal as there has been no regional journal of rehabilitation medicine in Southeast Asia (SEA). And, there are two national journals, the J Thai Rehabil Med which has been published mainly in Thai since 1991 and the Indonesia J Phys Med Rehabil, published in English since 2012. After some years of discussion among leading members of the ASEAN Rehabilitation Medicine Association (ARMA), there have been two main issues raised: 1) exchanging staff and residents in training, and 2) publishing a regional journal. The first issues have been achieved. However, to publish a new regional medical journal, starting from zero, is not an easy task. It requires good collaboration and lots of effort. Therefore, in preparation for becoming a regional journal, last year we invited physiatrists/rehabilitation physicians in academic institutes from Indonesia and Malaysia to join the editorial board, revised the aims of the Journal and called for English manuscripts of original articles, review articles, special articles and case reports related with rehabilitation medicine, rehabilitation services, system, policy and innovations from ASEAN countries. Early this year, the Thai Rehabilitation Medicine Association (TRMA) and the Royal College of Physiatrists of Thailand agreed to change the title of the Journal and in the year of 2019, the first issue will be under the new title of “the ASEAN Journal of Rehabilitation Medicine” (ISSN: 2673-0308). This will be a continuation of the J Thai Rehabil Med. And all manuscripts published in this issue are under the ASEAN J Rehabil Med 2019, volume 29, number 1. We do look forward to having more English manuscripts submitted from ASEAN for peer review. During this transitional year, there will be both Thai and English manuscripts published in the Journal; and hopefully the ASEAN J Rehabil Med would publish only English manuscripts in 2020. It is a big challenge for the editor and the editorial board after being published for 28 years under the title of the Journal of Thai Rehabilitation Medicine to step forward from a national journal to a regional journal with a new title of “the ASEAN Journal of Rehabilitation Medicine. We do hope that the ASEAN J Rehabil Med will be a recognized medical journal in the field of rehabilitation medicine regionally and globally in the near future.